Post-Colonial Macau: hope and despair in a World Centre of Tourism and Leisure - Michael O’Regan (Via@)
The expansion of casino concessions and subsequent growth of employment and gross domestic product (GDP) per Capita in Macau after the 1999 handover from Portugal created an illusion of prosperity in a post-colonial territory of less than 30 sq. km. A Special Administrative Region (SAR) of the People’s Republic of China (PRC), it is the only place in China where adults can legally gamble in casinos. This paper, using interviews with local residents, argues that the imagined category of “World Centre of Tourism and Leisure” coined by local authorities’ masks an illicit occult economy. The paper argues that the miraculous swiftness of GDP per capital, employment and budget surplus growth, was a result of a new post-colonial elite looking backwards into its colonial past. The paper argues that while the “World Centre of Tourism and Leisure” is a political construct and key hegemonic project to keep citizens in a hyper-real world of simulacra and control, it is at the cost of everyday gossip, caution, self-censorship and demoralization.